2020
DOI: 10.23937/2643-3885/1710048
|View full text |Cite|
|
Sign up to set email alerts
|

Subtle Cavovarus Foot: A Missed Risk Factor for Chronic Foot and Ankle Pathologies

Abstract: This literature review investigated the subtle cavovarus foot with a search in Pubmed and Google Scholar using the following keywords: Subtle cavovarus foot, cavovarus foot or cavus foot and one or more of the following: Associations, injuries, ankle sprains, ankle instability, sports, plantar pressure, dynamic pedobarography, Tekscan and footprint, from January 1980 to February 2019. Subtle cavovarus foot can alter foot and ankle biomechanics but reference values are lacking for dynamic pedobarography assessm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…The calcaneal pitch angle is the angle between the line connecting the lowest two points on the lower surface of the heel bone and the horizontal plane. The sagittal plane angle of inclination of the heel bone is 10°–25° in people with normal arches and greater than 30° in people with cavus feet ( Benjamin et al, 2020 ). It has been shown that calcaneal pitch is positively correlated with peak heel pressure and negatively correlated with arch pressure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The calcaneal pitch angle is the angle between the line connecting the lowest two points on the lower surface of the heel bone and the horizontal plane. The sagittal plane angle of inclination of the heel bone is 10°–25° in people with normal arches and greater than 30° in people with cavus feet ( Benjamin et al, 2020 ). It has been shown that calcaneal pitch is positively correlated with peak heel pressure and negatively correlated with arch pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Although the cavus foot is commonly caused by neurological disorders, SCF is considered to be a variant of normal as common as flatfoot deformities ( Monoli and Graham, 2005 ). The Coleman block test detects if the heel varus for SCF is of primary origin or is secondarily caused by the plantarflexion of the first metatarsal ( Deben and Pomeroy, 2014 ; Benjamin et al, 2020 ). A one-inch block is placed under the heel and lateral border of the foot.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of athletes, it could be due to continuous pressure when a player jumps, runs, or tackles an opponent. Notably, according to a recent study by Benjamin et al [ 13 ], athletes with cavovarus feet are prone to repetitive trauma, which results in Zone 3 injuries. This study proposes the theory that the physical structure of an athlete’s foot could be one of the significant determinants of Jones-type fracture prevalence.…”
Section: Anatomy and Pathophysiology Of Fifth Metatarsal Fracturesmentioning
confidence: 99%
“…The medial longitudinal foot arch is flexible and flattens during impact acting as an important shock absorber [ 1 ]. This ability is limited by a flat foot arch (pes planovalgus) or high foot arch (pes cavovarus) increasing the risk of injuries [ 2 5 ]. Several clinical measurements are described for assessing foot posture [ 6 , 7 ], but Foot Posture Index (FPI) is the recommended assessment tool as it evaluates the posture of the whole foot [ 8 ].…”
Section: Introductionmentioning
confidence: 99%